2017
DOI: 10.1080/00220973.2017.1315711
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Instruction for Spelling Performance and Spelling Consciousness

Abstract: This study examined the role of instruction for spelling performance and spelling consciousness in the Dutch language. Spelling consciousness is the ability to reflect on one's spelling and correct errors. A sample of 115 thirdgrade spellers was assigned to a strategy-instruction, strategic-monitoring, self-monitoring, or control condition representing different types of metacognitive aspects. The results showed that students in all three training conditions made more progress in both spelling performance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
1
6
0
1
Order By: Relevance
“…In other words, learners in the experimental group retained higher scores than the learners in control group. This implies that there has been a consistency between the results of this study and the findings reported in earlier studies by Zohrabi and Kaashef (2017), O'Sullivan and Thomas (2007), Lenks and Verbruggen (2010), Snowling (2000), Gentry (2004), Cordewener, Hasselman, Verhoeven, andBosman (2018). Consequently, it could be claimed that the findings of this study has been endorsed by other researchers' findings, stipulating the appropriate teaching techniques selected, prepared and employed to improve learners' spelling strategies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, learners in the experimental group retained higher scores than the learners in control group. This implies that there has been a consistency between the results of this study and the findings reported in earlier studies by Zohrabi and Kaashef (2017), O'Sullivan and Thomas (2007), Lenks and Verbruggen (2010), Snowling (2000), Gentry (2004), Cordewener, Hasselman, Verhoeven, andBosman (2018). Consequently, it could be claimed that the findings of this study has been endorsed by other researchers' findings, stipulating the appropriate teaching techniques selected, prepared and employed to improve learners' spelling strategies.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, Oller (1971) explained more by arguing that a test of dictation taps directly the process involved in the comprehension of language. Furthermore, Cordewener, Hasselman, Verhoeven, and Bosman (2018) examined the role of instruction for spelling performance and spelling consciousness in the Dutch language and found that the students in all three training conditions _ strategy-instruction, strategic-monitoring, self-monitoring, or control condition_ made more progress in both spelling performance and spelling consciousness than students in the control condition. Meanwhile, Kimura (2016) developed a six-minute partial dictation test and demonstrated that its quality had been good enough to be used as constituent of a placement test.…”
Section: Dictationmentioning
confidence: 99%
“…Alhaysony, 2012 also recommended adequate English writing practices in order to reduce spelling errors in the writeups of EFL students. Students' spelling consciousness and spelling performance improves with conscious effort, multiple practice opportunities, and providing immediate corrective feedback on spelling accuracy from teacher (Cordewener, Hasselman, Verhoeven, & Bosman, 2018). In this regard, a spellcheck may function as a learners' proofreading tool for spelling, as it spots most English spelling errors by showing a red curvy underline and giving accurate spelling suggestions before they become printed typos.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…MVRC has the potential to re-adjust the pendulum of pedagogy, away from an over-emphasis on content-rich activities of literacy, and toward a focus on the mechanics of decoding. MVRC is based on the idea that training in foundational skills can improve reading fluency more so than mere reading practice (Bosman and Van Orden, 1997;Mellard et al, 2010;Huo and Wang, 2017;Cordewener et al, 2018). Given this theoretical commitment, MVRC does not consider students' preferences about what to read, and there are no choices about lessons and practice activities.…”
Section: Reading Fluency and The Importance Of Basic Reading Skillsmentioning
confidence: 99%